1990
DOI: 10.1111/j.2042-3306.1990.tb04264.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of phenylbutazone on the intestinal mucosa of the horse: a morphological, ultrastructural and biochemical study

Abstract: Summary Phenylbutazone, a non‐steroidal anti‐inflammatory drug known to produce intestinal erosions, was administered intravenously (13.46 mg/kg bodyweight) to 12 horses which were killed after 24, 48, 72 and 96 h. Eight untreated horses served as controls. Annular erosions in the duodenum and mucosal necrosis in the colon were seen after 48 h which progressed in severity. The erosions were characterised by sloughing of the surface epithelium, subepithelial cleft and bleb formation, necrosis of the lamina prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
2
5

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 36 publications
2
25
2
5
Order By: Relevance
“…for longer than seven to ten days [15,10]. However, in one study, RDC was induced in two horses by administering 6 mg/kg bwt phenylbutazone s.i.d.…”
Section: Minireview Of the Literaturementioning
confidence: 99%
“…for longer than seven to ten days [15,10]. However, in one study, RDC was induced in two horses by administering 6 mg/kg bwt phenylbutazone s.i.d.…”
Section: Minireview Of the Literaturementioning
confidence: 99%
“…2 Experimentally, some horses treated with phenylbutazone at 4.4 mg/kg three times daily IV for 12 days developed colonic mucosal erosions associated with thrombosis and disruption of blood vessel walls in the lamina propria. 8 The colonic erosions in this horse may have been caused by the phenylbutazone treatment, and the lesions may then have compromised mucosal integrity sufficiently to allow infection by resident luminal A. equuli. The erosive colonic lesions themselves were small and should not have in themselves caused death.…”
Section: Brief Communications and Case Reportsmentioning
confidence: 99%
“…It is difficult to extrapolate in vitro data to in vivo concentrations. Concentrations used in studies 16,24,25 that evaluated the effect of NSAIDs in horses were similar to those used in the study reported here. In 1 of those studies, 16 flunixin meglumine and etodolac were compared.…”
Section: Discussionmentioning
confidence: 95%